Sport Injuries In Iraqi Governorate Clubs For Sitting Volleyball - Hatem, Bilal (Journal of Physical Education, 2018)
Sport Injuries In Iraqi Governorate Clubs For Sitting VolleyballThe research aimed at identifying the most common sport injuries as well as the bodily part which is mostly liable to injury, and the player's position which is mostly liable to injury. The researcher used the descriptive method. The research sample were (93) disabled sport players from eleven sport clubs and subcommittees in the Iraqi governorates who participated in the volleyball league 2017-2018. The subjects were 43 sitting volleyball players who suffered from sport injuries and were treated in sport medicine centers. The researcher concluded that muscle cramps and rupture are the most common injuries among volleyball players. in addition to that, he concluded that the shoulder is the most liable part of the body to injury. Finally the researcher concluded that the lack of efficient warm up is the main reason for injuries in sitting volleyball and that position 4 (outside hitter) is the most liable to injury. The researcher recommended performing a complete professional warm up, especially the shoulders, before starting training.